2009
DOI: 10.1080/14756360802166921
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of rat liver cathepsins B and L by the peptide aldehyde benzyloxycarbonyl-leucyl-leucyl-leucinal and its analogues

Abstract: Cathepsins B and L belong to the papain superfamily of cysteine proteases and play important roles in various physiological and pathological processes. In the course of studies on their inhibitors, we examined the inhibitory effects of the peptide aldehyde benzyloxycarbonyl-leucyl-leucyl-leucinal (ZLLLal) and its analogues. As a result, rat liver cathepsins B and L were shown to be strongly inhibited by them. The concentration required for 50% inhibition (IC 50 ) by ZLLLal was 88 nM for cathepsin B and 163 nM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…3F). Importantly, it has been reported that MG132 is also an efficient inhibitor of cysteine cathepsins (Ito et al, 2009), which we confirmed in HeLa cells using our microtiter assay for total catB/L and catC activity measurements (strategy 1) ( Fig. 3G).…”
Section: Llome Causes Rapid Loss Of Cysteine Cathepsin Activities Andsupporting
confidence: 84%
“…3F). Importantly, it has been reported that MG132 is also an efficient inhibitor of cysteine cathepsins (Ito et al, 2009), which we confirmed in HeLa cells using our microtiter assay for total catB/L and catC activity measurements (strategy 1) ( Fig. 3G).…”
Section: Llome Causes Rapid Loss Of Cysteine Cathepsin Activities Andsupporting
confidence: 84%
“…Thus, the dilution factor of a substance systemically injected into a honeybee is maximally 1:70. Given this dilution factor, the effective amount of inhibitor we injected in the behavioral experiments (1 μmol l −1 :70, which is equal to 14 nmol l −1 ) was lower than the doses of MG132 and β-lactone reported to effectively inhibit the ATP-dependent Lon protease, which has an IC 50 of 20 μmol l −1 for MG132 and an IC 50 of 3 μmol l −1 for β-lactone as well as other nonproteasomal proteases reported to be affected by either MG132 or β-lactone (Granot et al, 2007;Ito et al, 2009;Ostrowska et al, 2000;Tsubuki et al, 1996).…”
Section: Dilution Of Substances Systemically Injected Into Honeybeesmentioning
confidence: 99%
“…The reason for this contradiction remains unclear. MG132 is an inhibitor of the proteasome, but also blocks other proteases (Granot et al, 2007;Ito et al, 2009;Tsubuki et al, 1996). Accordingly, one possible explanation might be that one of the other proteases affected by MG132 is responsible for the effect on LTM formation.…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin B enzymatic activity is inhibited by alpha-macroglobulin from the cystatin family of inhibitors of papain-like cysteine peptidases, and by representatives of the equistatin family [24] . There are three additional groups of naturally occurring cathepsin B inhibitors: the aziridinyl peptides, peptide epoxysuccinyls, and peptide aldehydes [25,26] . Known synthetic cathepsin B inhibitors can be divided into groups of compounds, which contain either flavonoids, cyclic sulfates, or nitriles [27,28] .…”
Section: Introductionmentioning
confidence: 99%